Analysis of Madurese Cattle Consumer Preferences (Case Study of Purnomo Sapimulyo Farm in Boyolali District) - Julisna, Wanda; Mahananto; Prasetyo, Agung (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2025)
The agricultural sector includes a variety of plant and animal production activities to meet human needs, including the livestock subsector which plays an important role in the economy. In Indonesia, beef cattle farming, especially in Madura, has great potential in improving people's welfare and meeting the growing demand for protein. Consumer preferences are the choice likes or dislikes of a product, which is influenced by various factors such as shape, taste, and texture. Understanding consumer preferences can help improve customer satisfaction, develop more effective marketing strategies, and produce products that are more in demand. This study aims to examine the characteristics of the respondents and examine the attributes of Madura cattle which are consumer preferences in Purnomo Sapimulyo Farm, as well as examine the attributes that consumers consider most in the purchase decision of Madura cattle. The fishbein multi-attribute analysis method showed that the most considered attribute by consumers when buying Madura cattle was meat texture with an average value of 2.78. Purchase decisions based on the highest value to the lowest value are meat texture, price, weight, service, promotion and skin color